2018
DOI: 10.1111/lre.12202
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study ofLabeo victorianus(Bouelenger, 1901) andOreochromis niloticus(Linnaeus, 1758) grown in polyculture systems

Abstract: A polyculture experiment with African carp (Labeo victorianus) and Nile tilapia (Oreochromis niloticus) was conducted for 24 weeks in 12 earthen ponds measuring 150 m2 to assess their compatibility. Monoculture treatments T1 and T4 for L. victorianus and O. niloticus, respectively, were the controls for the two species, while treatments T2 and T3 were a polyculture of L. victorianus and O. niloticus at a ratio of 1:2 and 2:1, respectively. All treatments were carried out in triplicate, with feedings performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In this study, the O. jipe species displayed a remarkable reduction in feed intake immediately after the rains, which might have resulted in the observed low DO levels in this culture treatment. The same phenomenon has been reported in other cultured fish, such as Labeo victorianus by [24], in which the accumulation of unconsumed feed remnants resulted in prolonged low DO levels in the culture ponds, which stressed the fish, resulting in decreased growth and survival rates. Several studies have reported a decline in fish weight gain which has been attributed to decreased water temperatures during cold seasons characterized which directly affect feed intake [21,25].…”
Section: Growth and Survival Ratessupporting
confidence: 78%
“…In this study, the O. jipe species displayed a remarkable reduction in feed intake immediately after the rains, which might have resulted in the observed low DO levels in this culture treatment. The same phenomenon has been reported in other cultured fish, such as Labeo victorianus by [24], in which the accumulation of unconsumed feed remnants resulted in prolonged low DO levels in the culture ponds, which stressed the fish, resulting in decreased growth and survival rates. Several studies have reported a decline in fish weight gain which has been attributed to decreased water temperatures during cold seasons characterized which directly affect feed intake [21,25].…”
Section: Growth and Survival Ratessupporting
confidence: 78%
“…Cold water culture involves Rainbow trout ( Oncorhynchus mykiss ) in the Mount Kenya region while warm water fishes comprises of Nile tilapia ( Oreochromis niloticus ) constituting 75%, African catfish ( Clarias gariepinus ), and other species comprising 25% [5], [6]. There have been efforts to culture some indigenous fish, like the African carp ( Labeo victorianus ), Ngege ( O. esculentus and Victoria tilapia ( O. variabilis ) [7], [8], [9]. However, culture of these indigenous species have remained on experimental basis and are not widely adopted by farmers due to low survival and poor yields [2], [7].…”
Section: Introductionmentioning
confidence: 99%
“…There have been efforts to culture some indigenous fish, like the African carp ( Labeo victorianus ), Ngege ( O. esculentus and Victoria tilapia ( O. variabilis ) [7], [8], [9]. However, culture of these indigenous species have remained on experimental basis and are not widely adopted by farmers due to low survival and poor yields [2], [7].…”
Section: Introductionmentioning
confidence: 99%
“…This justifies the reason why Kenyan warm water aquaculture is dominated by the farming of the two species (Opiyo et al., 2018). Despite having the potential, the culture of indigenous fish species like L. victorianus , O. esculentus and O. variabilis has not been widely adopted by farmers because of their low production levels and survival (Munguti et al., 2014; Orina et al., 2018).…”
Section: Discussionmentioning
confidence: 99%